Synthesis of Ce/Mo-V4O9 nanoparticles with superior visible light photocatalytic activity for Rhodamine-B degradation. Issue 2 (April 2018) - Arunadevi, R.; Kavitha, B.; Rajarajan, M.; Suganthi, A.
Graphical abstract: Highlights: Cerium and Molybdenum Co-doped V4 O9 nanoparticles, evidenced by various characterization. Ce/Mo-V4 O9 nanoparticles were synthesized using a co-precipitation method. The Ce and Mo codoped V4 O9 has excellent photocatalytic activity of Rhodamine-B degradation. The high photocatalytic activity was caused by the synergistic effects between Ce doping and Mo doping. Photocatalytic dye degradation mechanism of codoped V4 O9 was proposed. Abstract: The role of Ce/Mo-V4 O9 nanoparticles and the possible active species in the Rhodamine-B degradation over the visible-light-driven Ce/Mo-V4 O9 catalyst have firstly been investigated in this work. The samples were characterized by UV–visible-diffuse reflectance spectroscopy (UV–vis-DRS), powder X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS), high resolution transmission electron microscopy (HR-TEM) and X-ray photoelectron spectroscopy (XPS) techniques. The results indicated that the doping element did not affect the final crystalline structure of V4 O9, but it had great influences on the photocatalytic activity of Ce/Mo-V4 O9 towards rhodamine-B (Rh-B) degradation. Factors such as pH, initial Rh-B concentration and catalyst dosage that may affect the photodegradation of Rhodamine-B were studied. More importantly, the codoped V4 O9 significantly improved the separation efficiency of the photogenerated electron-hole pairs. These factors contribute to the enhancement of photocatalytic activity. A possible mechanism was also proposed to understand the origin of enhanced performance in the codoped system. On the basis of radical scavenger experiments, superoxide radicals and holes are suggested to play a critical role in Rh-B degradation over Ce/Mo-V4 O9 . Overall, this work could provide new insights in to the synthesis of Ce/Mo-V4 O9 nanoparticles as high performance photocatalyst and promise as a visible light photocatalyst for dye waste water treatment.